Correlating environmental DNA and hydroacoustic estimates of biomass and abundance to monitor the globally Endangered mulloway (Argyrosomus japonicus) - Rourke, Meaghan L.; Broadhurst, Matt K.; Fowler, Ashley M.; Hughes, Julian M.; DiBattista, Joseph D.; Sawynok, Stefan; Furlan, Elise M. (Frontiers in Fish Science, 2025)
Monitoring long-term spatiotemporal changes in populations of vulnerable species requires non-lethal methods. Here we investigate the utility of environmental DNA (eDNA) for estimating the relative biomass and abundance of the globally Endangered mulloway (Argyrosomus japonicus) in a southeastern Australian estuary. During minimal tidal movement, 10 parallel transects at each of 12 sites were surveyed, involving water samples being collected for determining eDNA concentrations of mulloway DNA prior to hydroacoustics being used to estimate their abundance and then biomass. There was no significant linear relationship between eDNA and abundance but there was for biomass, although the direction of differences varied seasonally, with positive and negative regressions observed during autumn and spring, respectively. As non-invasive survey methods, both eDNA and hydroacoustics require further validation, and such efforts should assess the influence of key environmental factors.